Factors Associated With Negative Conversion Of Rt-Pcr Covid-19 - Ardea Safira; MUHAMMAD JAUHAN SYAH BACHTIAR (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2022)
The coronavirus disease 2019 (COVID-19) was declared an International Public Health Emergency (PHEIC) on 30 January 2020 by WHO. Many studies have analysis the clinical, radiological, laboratory profile, and treatment strategies of COVID-19, but there are still no studies on the factors that influence the negative conversion (NCT) of RT-PCR for COVID-19 in Indonesia. This type of study was cross-sectional and included 25 confirmed COVID-19 inpatients at Aminah Hospital Sidoarjo with a median NCT 8 days from initial hospital admission. Men need longer conversion time than women (p-value 0.044). The severity of COVID-19 and patient comorbidities were significantly associated with NCT of COVID-19 RT-PCR (p-value 0.035). Patients with severe severity at baseline had a longer conversion time (9 days) than those with moderate (8 days) and mild (7 days). Patients with comorbidities (diabetes, hypertension, or both) required longer NCT of RT-PCR (9 days) than those without comorbidities (7 days). The results of the log-rank test of age, leukocyte count, platelets, hemoglobin, lymphocyte and granulocyte percentages did not have a significant relationship with NCT of RT-PCR. Gender, case severity, and comorbid history of COVID-19 patients are factors that are associated with COVID-19 RT-PCR conversion time. Keywords: Factor, Conversion, RT-PCR COVID-19